Capturing the mechanics of clathrin-mediated endocytosis. (August 2022) - Smith, Sarah M.; Smith, Corinne J.
Abstract: Clathrin-mediated endocytosis enables selective uptake of molecules into cells in response to changing cellular needs. It occurs through assembly of coat components around the plasma membrane that determine vesicle contents and facilitate membrane bending to form a clathrin-coated transport vesicle. In this review we discuss recent cryo-electron microscopy structures that have captured a series of events in the life cycle of a clathrin-coated vesicle. Both single particle analysis and tomography approaches have revealed details of the clathrin lattice structure itself, how AP2 may interface with clathrin within a coated vesicle and the importance of PIP2 binding for assembly of the yeast adaptors Sla2 and Ent1 on the membrane. Within cells, cryo-electron tomography of clathrin in flat lattices and high-speed AFM studies provided new insights into how clathrin morphology can adapt during CCV formation. Thus, key mechanical processes driving clathrin-mediated endocytosis have been captured through multiple techniques working in partnership.